Improving the Students’ Achievement in Reading Comprehension by Using Inquiry Technique - Gigin Sappena Ginting; Siti Aisah Ginting (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2013)
This study attemps to imorove the students’ achivement in reading comprehension through inquiry technique. The study was conducted by using classroom action research. The subjects of the research were the 45 students of Grade XI SMA Negeri 1 Bahorok. It was conducted in two Cycles and consisted of six meetings.The instruments for colecting data used Reading Comprehension tests for quantitative data and Diary Notes, Interview Sheet, and Observation Sheet for qualitative data. Based on the Reading Comprehension score, students score in pre test, kept improving in every test. Based on Diary Notes, Observation sheet and Interview Sheet, it was found that the students were actualy involved in reading process. The results of the reasearch showed that Inquiry Technique can improve the students’ achivement in Reading Comprehension. In orientation test the mean of the students’ score was 53, the mean of the students’ score in Cycle I was 62.07, and the mean of the students’ score in Cycle II was 71.6. Based on the Observation Sheet, Diary Notes, and Interview Sheet, it was found that the teaching-learning process run well. The conclusion is that Inquiry Technique improved the students’ reading Coprehension and it is suggested to the English teacher to apply Inquiry Technique in Reading Comprehension. Keywords : Improving, students’ achievement, Inquiry Technique